ARAHAN PENGEMBANGAN PELAYANAN TERMINAL BINAYA KOTA MASOHI: Studi Kasus: Terminal Binaya, Kecamatan Kota Masohi, Kabupaten Maluku Tengah - Kezia Julia Lappy; Pieter Th. Berhitu; Fienkan L.S Dumalang (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Binaya Terminal is a Type C terminal that functions as a land transportation hub in Masohi City, Central Maluku Regency. The terminal's existing condition shows non-compliance with facility standards under Minister of Transportation Regulation No. 24 of 2021, in both main and supporting facilities. Public perception of terminal services also tends to be low, particularly in the aspects of comfort, information availability, and facility adequacy. This study aims to identify the existing condition of terminal facilities, analyze public perception of services, and formulate a service-development direction for Binaya Terminal. The study used a mixed-methods approach, combining field observation and regulatory review for qualitative analysis with a questionnaire distributed to 100 terminal-user respondents for quantitative analysis. Perception data were analyzed using a Likert scale and Importance-Performance Analysis (IPA) across 23 indicators within 6 aspects, while the development direction was formulated using quantitative SWOT analysis based on the IFAS–EFAS matrix. Results show that some main and supporting facilities are available but do not yet meet Type C terminal service standards. The IPA results placed 8 of 23 items in Quadrant I (top development priority), with the lowest suitability level (TKi) found in medical-room facilities (39.75%) and departure/arrival information systems (45.25%). The SWOT analysis produced coordinates (–0.26 ; +0.51), placing Binaya Terminal in Quadrant II of the SWOT diagram with a recommended Turn Around (WO) strategy. The resulting development direction covers physical quality improvement, strengthening of security and safety systems, provision of digital information media, vehicle-circulation reorganization, and improvement of terminal service management, to be implemented in three development phases toward Type B terminal status by 2032.